Regulation of Neural Precursor Cell Fate by the E2f3a and E2f3b Transcription Factors - Julian, Lisa (Université d'Ottawa / University of Ottawa, 2013)
The classical cell cycle regulatory pathway is well appreciated as a key regulator of cell fate determination during neurogenesis; however, the extent of pRB/E2F function in neural stem and progenitor cells is not fully understood, and insight into the mechanisms underlying its connection with cell fate regulation are lacking. The E2F3 transcription factor has emerged as an important regulator of neural precursor cell (NPC) proliferation in the embryonic and adult forebrain, and we demonstrate here that it also influences the self-renewal potential of NPCs. Using knockout mouse models of individual E2F3 isoforms, we demonstrate the surprising result that the classical transcriptional activator E2F3a represses NPC self-renewal and promotes neuronal differentiation, while E2F3b promotes the expansion of the NPC pool and inhibits differentiation. We attribute these opposing activities to a unique mechanism of transcriptional regulation at the Sox2 locus, a key regulator of stem cell pluripotency, whereby E2F3a recruits transcriptional repressors to this site, and E2F3b promotes Sox2 activation. Importantly, E2F3a-mediated Sox2 regulation is necessary for cognitive function in the adult. Additionally, through the determination of genome-wide promoter binding sites for E2f3 isoforms as well as E2F4, another key regulator of NPC self-renewal, we determined that E2Fs are poised to regulate an extensive set of target genes with key roles in regulating diverse cell fate choices in NPCs, including self-renewal, cell death, progenitor expansion, maintenance of the precursor state, and differentiation. Together, these results reveal a diversity of function for E2Fs in the control of neural precursor cell fate, and identify E2F3 isoforms as important regulators of the pluripotency and stem cell maintenance gene Sox2.
Keywords: Neural stem cell; E2f; Transcription; Sox2; Neurogenesis; Gene regulation; Brain development